2015
DOI: 10.5430/jnep.v5n6p50
|View full text |Cite
|
Sign up to set email alerts
|

New RN residency program to improve clinical competency, confidence, and socialization skills of novice nurses

Abstract: Objective: The transition to practice experience provides a useful process to integrate nursing knowledge, skills, and attitudes of newly graduated nurses before they assume the professional nurses' roles. The study examined the levels of perceived clinical competency, confidence, and professional role development skills of 114 culturally diverse novice nurses enrolled in 12-15 weeks of a collaborative RN residency program at a state funded California university during academic years 2009-2013. Methods: Descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This improvement could be partly explained by constant reassurance and psychological support that were given to interns by mentors and friendship attitudes between them that allow interns to feel free to discuss anything about their fears and anxieties with their mentors without hesitations. Similarly, another study that was conducted by Kim, et al, (2015) reported that mentoring leads new interns to feel that they have the freedom to express and communicate any of their concerns and anxieties and limiting the phenomenon of "keeping things bottled in.…”
Section: Discussionmentioning
confidence: 99%
“…This improvement could be partly explained by constant reassurance and psychological support that were given to interns by mentors and friendship attitudes between them that allow interns to feel free to discuss anything about their fears and anxieties with their mentors without hesitations. Similarly, another study that was conducted by Kim, et al, (2015) reported that mentoring leads new interns to feel that they have the freedom to express and communicate any of their concerns and anxieties and limiting the phenomenon of "keeping things bottled in.…”
Section: Discussionmentioning
confidence: 99%
“…Programmes resulting in improved practice and retention include specified resource people for new graduates, mentorship, formal education, and peer support opportunities (Rush et al, 2013). Some nursing residency programmes are conducted in collaboration with a university, such as that described by Kim, Young-Lee, Eudey, Lounsbury, & Wede et al (2015), but there is a gap in research literature about new graduate programmes that include Masters level academic credits . However, literature does reveal that formal education leading to postgraduate university qualifications supports nurses' personal and professional development (Cooley, 2008;Covell, 2009;Drennan, 2008) and to be the most appropriate preparation for advanced nursing practice roles (Aitken, Currey, Marshall, & Elliott, 2008;Currie & Watterson, 2009;Wilson-Barnett, 2006).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“… Washington (2012 ) stated that lack of clinical experience and complex nursing care methods cause functional anxiety. Stress and lack of confidence in new graduate nurses affect their ability to provide quality care ( Kim et al, 2015 ). Clark and Springer (2012 ) reported that a lack of knowledge and fear of harming patients reduce nurses’ self-confidence.…”
Section: Introductionmentioning
confidence: 99%